If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(y + -1) = 2(3y + 1) Reorder the terms: 7(-1 + y) = 2(3y + 1) (-1 * 7 + y * 7) = 2(3y + 1) (-7 + 7y) = 2(3y + 1) Reorder the terms: -7 + 7y = 2(1 + 3y) -7 + 7y = (1 * 2 + 3y * 2) -7 + 7y = (2 + 6y) Solving -7 + 7y = 2 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -7 + 7y + -6y = 2 + 6y + -6y Combine like terms: 7y + -6y = 1y -7 + 1y = 2 + 6y + -6y Combine like terms: 6y + -6y = 0 -7 + 1y = 2 + 0 -7 + 1y = 2 Add '7' to each side of the equation. -7 + 7 + 1y = 2 + 7 Combine like terms: -7 + 7 = 0 0 + 1y = 2 + 7 1y = 2 + 7 Combine like terms: 2 + 7 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| x-2(2x+10)=12 | | 3x+7/2=8 | | A=2(l+1) | | 1/2(12n-8)=26 | | A=x+y | | -21+x=5+4(1+4x) | | 2/5(5k+35)-8=12 | | -2-2+4x=5-6x | | (4x-3)(5x+2)= | | -(2+11)=11-2t | | -3x-8+4x=-17 | | .4(3d-5)=4 | | x+-7=12 | | 2(4r+3)-3(r+5)= | | -3r+15= | | -(2n+6)=-3-3n | | x-(-1)=-5 | | 6x(5x+5)=-3 | | 3.8m-5-3.8m-3= | | 4(2h+1)+3(4h+7)= | | -9(5x+18)=243 | | 180=-6(7x+12) | | 4x+48=40+8+4x | | -312=-6(-7x-18) | | 9x-1*4x= | | -4x-4(x-1)=-32-4 | | 12+2p=3(4-5p) | | 2b-4-6b-6= | | 2.4h+1=7 | | -10n+3(8+8n)=-6(n+4) | | 75=42-3x | | 2(x-2)+3x=-6-8 |